1989
DOI: 10.3354/dao006121
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal steatosis in the farm-reared sea bass Dicentrarchus labrax

Abstract: Light microscopy, scanning and transmission electron microscopy were used to study the anterior intestine of the sea bass Dicentrarchus labrax L., involved in lipid absorption. In the first part of the study, intestinal morphology of control feral fishes was described and lipid absorption through the intestinal mucosa was defined by comparing starved and fed individuals. In the second part, similar investigations were made on specimens reared on artificial food. These show injuries of the mucosa, ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
3
28
0
3
Order By: Relevance
“…This observation agrees with that of Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Kozarić et al (2004), in Merluccius merluccius, andOlsen et al (2005), in Oncorhynchus mykiss, who stated that the presence of the endocytotic vesicles in the rectal enterocytes may be a complement to the luminal protein digestion by absorbing protein macromolecules. Moreover, Gargiulo et al (1998), in Tilapia spp, suggested that the endocytosis is followed by the intracellular digestion by the lysosomes.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 80%
See 1 more Smart Citation
“…This observation agrees with that of Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Kozarić et al (2004), in Merluccius merluccius, andOlsen et al (2005), in Oncorhynchus mykiss, who stated that the presence of the endocytotic vesicles in the rectal enterocytes may be a complement to the luminal protein digestion by absorbing protein macromolecules. Moreover, Gargiulo et al (1998), in Tilapia spp, suggested that the endocytosis is followed by the intracellular digestion by the lysosomes.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 80%
“…These observations suggest that the enterocytes of the anterior portion of the intestine are involved in lipid absorption. This suggestion is in accordance with that of Stroband and Debets (1978), in Ctenopharyngodon idella, Anderson (1986), in Girella tricuspidata, Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Gallagher et al (2001), in Lagodon rhomboids, Caballero et al (2003), in Sparus aurata, Kozarić et al (2004), in Merluccius merluccius, and Carrassón et al (2006), in Dentex dentex. Moreover, Fontagné et al (1998), in Cyprinus carpio, stated that the intestinal fat droplets can be interpreted as a temporary storage form of the re-esterified fatty acids.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 75%
“…REQUIREMENT Fish probably have an absolute requirement for phospholipids (PL), mainly phosphatidylcholine (PC) and possibly phosphatidylinositol (PI) (Coutteau et al 1997). The most striking example of this is seen in some marine larvae where lipid droplets tend to accumulate, sometimes in livers (Salhi et al 1999), but most commonly in enterocytes upon feeding with artificial or supplemented live feeds (Deplano et al 1989;Geurden et al 1997;Salhi et al 1999;Morais et al 2006;. The cause appears to be linked to impaired enterocyte lipoprotein synthesis where PC (and apolipoproteins) is needed to form a coat around the absorbed TAG enabling it to be transported out of the cell.…”
Section: Norwegian Scientific Committee For Food Safetymentioning
confidence: 99%
“…We have previously described (Deplano et al 1989) the absorption of lipids in the proximal intestine of the immature sea bass Dicentrarchus labrax. Con~parison of feral and farm-reared individuals revealed detenoration of the mucosa resulting in lipid overloading in enterocytes and intercellular spaces, mainly caused by artificial feed.…”
Section: Introductionmentioning
confidence: 99%